2017
DOI: 10.1111/cdev.12786
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic, Familial, and Religious Identity of Roma Adolescents in Bulgaria, Czech Republic, Kosovo, and Romania in Relation to Their Level of Well‐Being

Abstract: This study examines ethnic, national, familial, and religious identity and well-being of 632 Roma minority and 589 majority adolescents (age: M = 15.98 years, SD = 1.34) in Bulgaria, the Czech Republic, Kosovo, and Romania. Results indicated that Roma showed lower endorsement of national identity but stronger religious identity than their majority counterparts. Path models showed positive associations of familial and religious identities with well-being, whereas Roma identity was negatively associated with wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 72 publications
2
37
0
1
Order By: Relevance
“…One of the Dimitrova et al. () findings concurs with those of the other three studies: Familial identity was found to be strongly linked to well‐being in all Roma groups. Again, this shows that being able to rely on a positive interpersonal context is adaptive for development.…”
Section: Key Findingssupporting
confidence: 72%
See 4 more Smart Citations
“…One of the Dimitrova et al. () findings concurs with those of the other three studies: Familial identity was found to be strongly linked to well‐being in all Roma groups. Again, this shows that being able to rely on a positive interpersonal context is adaptive for development.…”
Section: Key Findingssupporting
confidence: 72%
“…The findings of the study by Dimitrova et al. () diverge remarkably from those of the three other studies. Dimitrova et al.…”
Section: Key Findingsmentioning
confidence: 55%
See 3 more Smart Citations